Website Design for Providing Product Price Information of Micro, Small, and Medium Enterprises (MSMEs) Retail Business - Sipahutar, Luat Paska; Findi, Muhammad; Neyman, Shelvie Nidya (Indonesian Journal of Multidisciplinary Science, 2025)
MSMEs dominate Indonesia’s economy, comprising 99.99% of business units, yet face challenges in digital adoption. This study addresses the gap by designing a website to streamline retail pricing information for Bekasi Regency’s MSMEs, leveraging rebranding and technology to enhance market reach. The research aims to develop a user-friendly website (www.produkumkmsejahtera.com) for price transparency, validate its effectiveness, and analyze MSME digital engagement. Conducted from November 2024 to January 2025, the research employed a mixed-method approach: surveys with 150 MSMEs, validity/reliability tests (Cronbach’s alpha 0.956), and iterative website development using CSS, HTML, JavaScript, and Laravel. Data collection included GPS-based price tracking and WhatsApp integration for customer interaction. The logo and responsive design significantly improved user engagement. Dominant sectors were crafts (weaving, leather) and food (presto milkfish). Validity tests confirmed robust metrics for information quality and trust. The study highlights the need for digital tools in MSME growth, recommending a future Play Store app with payment features. Findings support policymakers and MSMEs in adopting scalable digital solutions.